2021
DOI: 10.19087/jveteriner.2021.22.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Semen Beku Kambing Peranakan Boer yang Dikriopreservasi dengan Pengencer Tris Kuning Telur dan Berbagai Konsentrasi Ekstrak Daun Kelor

Abstract: Daun kelor mengandung berbagai zat nutrien yang dapat melindungi spermatozoa selama kriopreservasi semen. Tujuan penelitian ini adalah untuk menguji pengaruh ekstrak daun kelor di dalam pengencer tris kuning telur terhadap kualitas semen beku kambing peranakan Boer. Semen segar dibagi ke dalam empat buah tabung reaksi dengan volume yang sama, kemudian disentrifugasi dengan kecepatan 3.000 RPM selama 20 menit. Plasma semen dibuang, dan sedimen (spermatozoa) diencerkan dengan empat pengencer berbeda sebagai perl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…When compared with other breeds of goats, the semen volume of the Gembrong goat is relatively lower. Saburai goat semen volume is 0.78±0.4 ml [15], Kejobong goat semen volume is 0.60±0.20 ml [7], and Boer goat semen volume is 0.70±0,21 ml [19]. Variations in semen volume can be caused by differences in breed, age, body size, and collection frequency [20].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with other breeds of goats, the semen volume of the Gembrong goat is relatively lower. Saburai goat semen volume is 0.78±0.4 ml [15], Kejobong goat semen volume is 0.60±0.20 ml [7], and Boer goat semen volume is 0.70±0,21 ml [19]. Variations in semen volume can be caused by differences in breed, age, body size, and collection frequency [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kualitas semen segar merupakan tahapan dasar sebelum diberikan perlakuan, karena nilai kulaitas semen segar menjadi acuan tahapan penelitian selanjutnya. Persentase viabilitas yang diperoleh dalam penelitian ini adalah 88,54±2,11%, Hasil beberapa penelitian melaporkan bahwa persentase hidup spermatozoa semen hasil ejakulasi pada kambing PE adalah rata-rata 87.96±0.02% (Hidayati et al, 2015), 70±0,00 % , 95,82±0,23% (Ardiansyah et al, 2020), 81±1,22 % .…”
Section: Karakteristik Semen Segarunclassified
“…Gerakan massa spermatozoa yang dihasilkan adalah +++, pH 6,50±0,15, laporan ini sama dengan laporanAriantie et al (2014) gerakan massa +++, pH 6,73±0,23. Rizal et al, (2016) gerakan massa +++, pH 6,90±0,10 dan Suteky et al (2015) pH 6,83 ± 0,29 dan gerakan massa +++.…”
unclassified
See 1 more Smart Citation
“…Compared to other breeds of goats, the semen volume of Gembrong goat was relatively lower. Pamungkas et al [3] reported that the semen volume of Gembrong goats (0.5±0.1 ml) was lower than that of Etawah crossbred goats (1.23±0.29 ml) [4], Nubian (1.80±0 .52 ml) [5], Boer (1.34±0.3 ml) [6], and Boer (0.70±0.21 ml) [7], Saburai (0.78±0.4 ml) [8], and Kejobong (0.60± 0.20 ml) [9]. In addition, the semen quality of Gembrong goats was also reported to be lower than that of other goats in Indonesia, such as the Etawah crossbred goats with volume, motility, concentration, and normal spermatozoa morphology of 1.15±0.05 ml, 78.00±2.50%, 0.94±0.05 (x10 9 /ml), and 98.12±0.56%, Anglo Nubian 1.13±0.02 ml, 74.75±1.25%, 0.87±0.03 (x10 9 /ml) and 96.54±2.12%, Anpera 1.12±0.04 ml, 76.75 ±1.25%, 0.91±0.04 (x10 9 /ml) and 97.50±0.77% [10], Sapera 0.95±0.19 ml, 75.00±1.11%, 3545±95.01 (x10 6 /ml) 94, 50±1.05%, Saanen 1.22±0.23 ml, 77.00±4.83%, 3620±0.41 (x10 6 /ml), 89.83±4.62%, respectively [11].…”
Section: Introductionmentioning
confidence: 99%